Analisis Tingkat Partisipasi Dan Persepsi Anggota Afinitas Terhadap Program Desa Mandiri Pangan - Evi Andriani; Herri Fariadi (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2017)
One of the effort to tackle the problem of poverty and food insecurity, government agency food security through agriculture department, in 2006 has eilcis village self-food program. Village self-food program success depends on the participation of food and public perception as well as the approach taken by the government to the community in the planning, implementation, monitoring and evaluation. Has conducted research with the aim to analysis of the level member of affinity groups participation and perception for village self-food in Padang Serai village Kampung Melayu Bengkulu City. Research method using descriptive analysis is presented data or information in order to obtain a complete and deiled results. This information will be illustrated by some of the questions with three alternative answer. The answer given by level where: to answer (agree = S, Sometimes = KD, and does not agree = TS). Alternative answer will be rated based on the level (score) S = 3, KD =2, and TS = 1. Based on the results of the research village sel-food program in Padang Serai village Kampung Melayu Bengkulu City average of 28,13 which means that the level of participation of members of affinity included in the medium category. Most respondents participation is a class between 23,4-32,7 namely the medium category with a number of 21 people or 65,63. Whereas the respondent participation of at least between 14-23,3 is the low category. Totaling 5 respondents or 15,63%. Of data on the perception of respondents could be on average 33,06.This condition indicator that the member of afiniti group has a high or good perception of the village self-food program. The respondents perception that most of the classes between 32,7-42 is with his category with a number of 18 people or 56,25%. Whereas at least the perception of respondents between 14-23,4 is the low category, totaling 6 respondents or 18,75%.